2011
DOI: 10.3389/fncir.2011.00007
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Processing of Complex Mixtures Establishes a Unique Odor Representation in the Moth Antennal Lobe

Abstract: Animals typically perceive natural odor cues in their olfactory environment as a complex mixture of chemically diverse components. In insects, the initial representation of an odor mixture occurs in the first olfactory center of the brain, the antennal lobe (AL). The contribution of single neurons to the processing of complex mixtures in insects, and in particular moths, is still largely unknown. Using a novel multicomponent stimulus system to equilibrate component and mixture concentrations according to vapor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
73
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(84 citation statements)
references
References 67 publications
11
73
0
Order By: Relevance
“…However, the strong nonlinear interactions observed at the output of six of seven animals support conclusions concerning the important role of the modulatory interneuron network in insects (Hildebrand et al, 1992;Chou et al, 2010;Lei et al, 2011;Reisenman et al, 2011;Kuebler et al, 2011a,b), and thus strengthen the idea of a novel feature percept generated by the AL. Moreover, these results are consistent with our previous electrophysiological study at the single neuron level (Kuebler et al, 2011b) and indicate that the mechanisms of mixture processing revealed at the single neuron level are maintained across the glomerular array in the AL.…”
Section: Input/output Comparison Reveals Spatiotemporal Modulationsupporting
confidence: 82%
See 4 more Smart Citations
“…However, the strong nonlinear interactions observed at the output of six of seven animals support conclusions concerning the important role of the modulatory interneuron network in insects (Hildebrand et al, 1992;Chou et al, 2010;Lei et al, 2011;Reisenman et al, 2011;Kuebler et al, 2011a,b), and thus strengthen the idea of a novel feature percept generated by the AL. Moreover, these results are consistent with our previous electrophysiological study at the single neuron level (Kuebler et al, 2011b) and indicate that the mechanisms of mixture processing revealed at the single neuron level are maintained across the glomerular array in the AL.…”
Section: Input/output Comparison Reveals Spatiotemporal Modulationsupporting
confidence: 82%
“…In contrast to honeybees (Fonta et al, 1993), most local neurons in Manduca show a typical broad "symmetrical" arborization pattern innervating the majority of AL glomeruli (Matsumoto and Hildebrand, 1981;Kuebler et al, 2011b;Reisenman et al, 2011). Consequently, an inhibitory global network incorporating a population of neurons with glomerulus-specific connectivity for general odor mixtures seems unlikely in Manduca (but compare the Manduca MGC: Christensen and Hildebrand, 1997;Lei et al, 2002;Heinbockel et al, 2004).…”
Section: Input/output Comparison Reveals Spatiotemporal Modulationmentioning
confidence: 99%
See 3 more Smart Citations